LINGUISTIC CHARACTERISTICS OF MALE AND FEMALE STUDENTS WITH DIFFERENT CULTURES IN USING LANGUAGE IN BOARDING HOUSE - Herois Theresyah Simaremare; Sri Minda Murni; Amrin Saragih (Universitas Negeri Medan, 2018)
This article aims to investigate the linguistics characteristics of male and female students with different cultures in using language in boarding house. The method of the study is descriptive qualitative research. Qualitative research focuses on understanding social phenomena and providing rich verbal descriptions of setting, situations, and participants. It means the data are in the form of words and sentences. The data is taken from 4 males and 4 females students who live in boarding house. The sample of this research will be taken through random sampling technique. This research has indeed revealed a unique gender differences between Bataknese and Karonese students. The results of this study find out that there are no consistent characteristics of male and female students with different cultures in using the language in boarding house. Male use the female’s linguistic characteristics, such as: declaration with interrogative intonation, tag question, emotional reference and high of politeness, vice versa, female uses the male’s linguistic characteristics, such as: direct, judgement adjectives, less of politeness and brief sentences. Indeed, this study find out that Bataknese female students are more dominant use male’s linguistic characteristics.Keywords:gender, linguistic characteristics, language use , culture, utterances